Therapeutic Potential of Chitosan Nanoparticles as Antibiotic Delivery System: Challenges to Treat Multiple Drug Resistance - Sivakumar, S. M. (Asian Journal of Pharmaceutics (AJP), 2016)
Antibiotic treatment for bacterial infection is becoming a big challenge due to the expression of a resistant factor which is a major hurdle in curing the infectious diseases, especially nosocomial infections. Globally, multiple drug resistance has emerged as a major public health problem. Nanotechnology is the most unique technology that can efficiently deliver the antibiotics to the cell site. In this review, we are focusing on the use of chitosan nanoparticles as an antibiotic delivery system to improve the therapeutic efficiency of antibiotics and to overcome the antibiotic resistance. We conclude that chitosan nanoparticles are promising therapeutic carriers to deliver antibiotics and can overcome efflux mechanism of bacteria.